Analisis Proses Bisnis Sertifikasi Halal Di Era Baru Sertifikasi Badan Penyelenggara Jaminan Produk Halal - Khairul Hafiz (Universitas Syiah Kuala, 2023)
Information technology at this time has developed very rapidly so that many government agencies in providing services use information systems, in this case government agencies digitize service systems. The Halal Product Assurance Organizing Agency (BPJPH) in accordance with the mandate of Law 33 of 2014 concerning Halal Product Assurance was established and provides services related to halal certificates. Of course, to carry out the mandate of the Law, the Halal Product Guarantee Agency (BPJPH) carries out a government service which is also supported by other Organizing stakeholders to provide halal certification